Structure-related differential proteins identification for sous-vide cooking hairtail (Trichiurus lepturus) product. Issue 11 (28th October 2020) - Li, Yuan; Huang, Jiayin; Zhou, Yaqi; Wu, Tiantian; Ma, Peihua; Yuan, Chunhong; Chen, Shiguo; Hu, Yaqin
Abstract : Optimal heating parameters for sous-vide cooking hairtail ( Trichiurus lepturus ) were selected and the differential proteins related to texture change were clarified using proteomics. Abstract : Optimal heating parameters for sous-vide cooking hairtail ( Trichiurus lepturus ) were selected and the differential proteins related to texture change were clarified using proteomics. Heating under 68 °C for 20 min was chosen to be the desirable heating parameter. Texture profile analysis (TPA) showed the texture of hairtail changed more severely during heat-up process than heating preservation process. Most of the high-content proteins did not change much during heating preservation. 169 kinds of proteins were identified as differential expressed proteins. Actin cytoplasmic 1, myosin heavy chain 1 and myosin heavy chain were the most variable structural proteins during heat-up process, with the change fold of 32.4, 29.1 and 18.8, respectively, while the highest structure proteins changing fold during heat preservation process were 16.7, 4.7 and 3.9, respectively, much lower than that of heat-up process. The partial deformation of structure-related proteins under sous-vide cooking was a vital factor in reserving the texture of hairtail.